2009
DOI: 10.1071/ah090062
|View full text |Cite
|
Sign up to set email alerts
|

The health care system as a social determinant of health: qualitative insights from South Australian maternity consumers

Abstract: Health systems and policies are important determinants of health because they influence the type and quality of health care available to a population. This study included semi-structured qualitative interviews and a questionnaire to collect demographic data and household details for a purposeful sample of 38 mothers and 24 fathers from four socioeconomic areas of metropolitan South Australia who had at least one child aged between 1 and 6 years of age.The participants reported that birth experiences within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
(21 reference statements)
1
16
0
Order By: Relevance
“…A small study of consumers undertaken in South Australia reported that birth experiences were at odds with the expectations of a significant number of women [22]. This finding was confirmed in a recent study of 141 Western Australian women's accounts of their birth experience with more descriptions of negative birth experiences than positive ones [25].…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…A small study of consumers undertaken in South Australia reported that birth experiences were at odds with the expectations of a significant number of women [22]. This finding was confirmed in a recent study of 141 Western Australian women's accounts of their birth experience with more descriptions of negative birth experiences than positive ones [25].…”
Section: Resultsmentioning
confidence: 80%
“…We live in a 'no risk' society [17] in which technology-intensive childbirth is equated with high standards of care employed in the best interest of women and babies [18]. Families have come to fear birth justifiably in light of the messages they receive from some health professionals, media and social networks reinforcing the belief that 'childbirth is inherently risky' [19-21], a 'difficult' process from which mothers and babies need to be rescued [22]. Parents know that they are not the experts in pregnancy and birth and that the consequences of any problems that may arise can be catastrophic [18].…”
Section: Introductionmentioning
confidence: 99%
“…18 Hence, women today prefer more input into their maternity care and are more willing to challenge the professional on their decisions and opinions. 18,23,24 Despite strong support by policy documents and claims by professionals to provide 'woman-centred care', the role of the patient or client in frameworks of collaborative models of care is often absent. 2,21 Rather than focusing on the client contribution to the collaborative process, frameworks seem to focus on how health professionals interact with each other.…”
Section: Professional Statusmentioning
confidence: 97%
“…This includes improving the rates of vaginal birth and breastfeeding. Funding that prioritises integrated services from antenatal through birth to postnatal care (a "Pregnancy-Parturition-Parenting" focus) and acknowledges the physiological and mental health lifecourse impact of birth experiences on infant, maternal and family health (Buist et al, 2008;Newman, 2009) will assist this objective. The first goal of the funding plan, 'what ought to be', must be oriented toward maximising outcomes in the short and long term for whole of population health (Lynch, 2011).…”
Section: Section 4: Better Systems Designmentioning
confidence: 99%
“…Research on the relationship between fertility and family size in Australia (Newman, 2009) also identifies unintended consequences of high levels of traumatic birth as a 'sleeper' issue affecting early parenthood and maternal and child health. Longer-term emotional and physical legacies also negatively impact family planning and the desire for further children, adversely affecting national fertility rates (Newman, 2009). BC analysis also therefore makes transparent the continuing lack of systemic intervention to reduce what are significant co-morbidities and negative impacts on life course health outcomes.…”
Section: Stakeholder Powermentioning
confidence: 99%